REVITALISASI BUDAYA TABE DALAM PERSPEKTIF KI HAJAR DEWANTARA SEBAGAI UPAYA MENGATASI DEGRADASI SOPAN SANTUN PESERTA DIDIK DI UPT SPF SDN PAMPANG - Fiqrah Syalwana Akbar; Maria Elisabeth Nona Veny; Sinam; Darwin Paonganan; Burhan; Achmad Fajar Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the phenomenon of declining politeness among students in the digital era, which is reflected in the gradual disappearance of the “Tabe” cultural practice within the school environment. The main problem identified at UPT SPF SDN Pampang is the low level of students’ ethics, both in behavior and speech, caused by the influence of social media content and the lack of filtering toward external cultures. This study aimed to formulate concrete and systematic strategies to revitalize the culture of Tabe’ through the perspective of Ki Hadjar Dewantara’s educational philosophy in order to restore students’ character and moral values. The methodology employed in this study was qualitative research with a phenomenological approach to explore more deeply the authentic experiences of teachers regarding changes in students’ behavior. The research subjects were selected through purposive sampling, namely classroom teachers who interact daily with students and thoroughly understand the students’ character conditions at school. Data collection techniques included in-depth interviews, participatory observations of students’ spontaneous behavior, and documentation of habituation activities. The findings revealed that the consistency level of students in practicing the Tabe’ culture ranged only from 10% to 40%. Efforts to revitalize this culture were carried out by providing direct role models (Ing Ngarsa Sung Tuladha), in which teachers consistently used expressions such as “Please,” “Sorry,” “Thank You,” and “Excuse Me.” In addition, the use of video and audio technology to introduce local songs containing moral messages, as well as collaboration between schools and parents, became key factors in guiding children according to their natural development and character. Therefore, it can be concluded that the revitalization of local wisdom integrated with the philosophy of national education can serve as an effective moral safeguard for students amid the challenges of social change and the digital era. Keywords: Ki Hadjar Dewantara, character education, politeness, elementary education, Tabe’ culture.